ANALYSIS OF THE MARKET SEGMENT – PRODUCTS OF MEDICAL TREATMENT OF INJECTABLE SYRINGES IN THE PHARMACEUTICAL MARKET OF THE REPUBLIC OF UZBEKISTAN (Neo Scientific Peer Reviewed Journal, 2023)
The medical device industry is the most important and fastest-growing segment of the healthcare industry. Medical device manufacturers produce a wide range of products, from complex diagnostic and therapeutic devices to simple medical devices for use in medical institutions. In recent times, many manufacturing companies in the industry have made significant technological advancements and have grown exponentially. The market continues to grow globally, despite strict regulations and financial pressure on the industry.For another 20-25 years, there have been only 3 enterprises in Uzbekistan that produce per-linking products and vata, and today there are more than 42 enterprises for the production of 97 names of interconnection devices. The number of enterprises specializing in the production of tys-bonding products and products from local raw materials is growing indefinitely, and their assets are expanding.Objective. The purpose of this study was to study and analyze the results of registration of a medical device - injection syringes presented in the State Register of the Republic of Uzbekistan.Materials and methods. At present, the domestic pharmaceutical industry is faced with the task of not only meeting domestic demand for medical products, but also increasing the export potential of the domestic pharmaceutical industry.In order to be competitive in a market economy, pharmaceutical companies must improve the quality of their products and continuously improve their quality assurance activities. Thanks to the adopted legislative and regulatory documents, the trend towards the substitution of imported products is being monitored.Results and discussion. In the Republic of Uzbekistan, strategies and national concepts in the areas of its application and development have been identified as priority areas of domestic health care, and part of this policy is a policy of continuous improvement of the quality of these areas.